Analysis of Crime News in The Jakarta Globe by Graduation Systems - Dien Novita (Metahumaniora, 2022)
This research looked into the Graduation systems in The Jakarta Globe's crime coverage. The study used mixed-method research and categorized six works. The Appraisal Systems Theory was used to examine the data. The study sought to determine the graduation systems of crime news in The Jakarta Globe, as well as to characterize the writer’s viewpoints on measuring the force of the message in crime news. According to the data, The Jakarta Globe presents 55% of the force dominantly. Furthermore, while reporting on crime, the authors of The Jakarta Globe utilize intensifier terms.